Is That Car Smiling at Me? Schema Congruity as a Basis for Evaluating Anthropomorphized Products - Aggarwal, Pankaj; McGill, Ann L. (Journal of Consumer Research, 2007)
The present research proposes schema congruity as a theoretical basis for examining the effectiveness and consequences of product anthropomorphism. Results of two studies suggest that the ability of consumers to anthropomorphize a product and their consequent evaluation of that product depend on the extent to which that product is endowed with characteristics congruent with the proposed human schema. Furthermore, consumers' perception of the product as human mediates the influence of feature type on product evaluation. Results of a third study, however, show that the affective tag attached to the specific human schema moderates the evaluation but not the successful anthropomorphizing of the product.